From multistakeholderism to digital sovereignty: Toward a new discursive order in internet governance? - Julia Pohle; Mauro Santaniello (Policy & Internet, 2024)
Since the early 2000s, the multistakeholder governance approach has been the reference model for transnational internet governance, reaching far beyond the original field of technical coordination and standard-setting. But over the last decade many countries, including democracies supportive of multistakeholderism, have adopted measures to strengthen their digital sovereignty. Thereby, they have been advancing discourses and practices that reinforce state power with regard to the digital and are often at odds with the multistakeholder model. This paper analyzes the emerging dialectic between multistakeholder internet governance and digital sovereignty by seeking to understand how the pursuit of digital sovereignty is increasingly challenging the hegemony of the multistakeholder discourse in internet governance. To this purpose, it reassesses the historical development of power struggles over the internet through the analytical lenses of the discourse coalition framework. After reconstructing how the multistakeholder discourse has emerged and institutionalized in the internet governance arena, the paper retraces the expansion of the digital sovereignty discourse, regarding both the actors promoting it and the narratives attached to it. It also identifies key motivations behind this discourse. Finally, the paper discusses whether the digital sovereignty discourse is emerging as a new discursive order in the internet governance field and draws attention to conditions that could either support or weaken its emergence.
Keywords: 320; digital policy; digital sovereignty; discourse coalition; internet governance; multistakeholderism